2022
DOI: 10.3389/fsurg.2022.891747
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Seven Fixation Methods for Sagittal Split Ramus Osteotomy with Four Advancement Levels by Finite Element Analysis

Abstract: BackgroundMandibular sagittal split ramus osteotomy (SSRO) is a routine surgery to correct mandibular deformities, such as mandibular retrusion, protrusion, deficiency, and asymmetry. However, nonunion/malunion of the fragments and relapse caused by fixation failure after SSRO are major concerns. Rigid fixation to maintain postosteotomy segmental stabilization is critical for success. Additionally, understanding the biomechanical characteristics of different fixation methods in SSRO with large advancements is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…Placing two miniplates reveals a better biomechanics outcome than placing only one miniplate with the same thickness. Previous studies have reported this result [34][35][36]. However, no studies have compared the biomechanics between one thicker miniplate and two thinner miniplates investigated in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Placing two miniplates reveals a better biomechanics outcome than placing only one miniplate with the same thickness. Previous studies have reported this result [34][35][36]. However, no studies have compared the biomechanics between one thicker miniplate and two thinner miniplates investigated in our study.…”
Section: Discussionsupporting
confidence: 58%
“…This process was automated using the AnyBody plugin called the “AnyFE Converter Tool for Abaqus” (detailed information is available at: https://www.anybodytech.com/resources/customer-downloads/ ). According to the contact method described in the reference, the threaded screw area was used for binding to the bone ( He et al, 2022 ). According to the report of Suzuki et al (2020) , meshes that included a 1-cm margin surrounding the osteotomy surface were degraded with weakening of the mesh material and simulated a callus during the bone healing process .…”
Section: Fe Simulationmentioning
confidence: 99%